A Study of Aedes aegypty Susceptibility Against Cypermetrin at Elementary Schools Yogyakarta - Anies Mulyani; Damar Tri Boewono; Tri Baskoro Tunggul Satoto (Pusat Kedokteran Tropis, 2017)
Introduction: Dengue Hemorrhagic Fever is transmitted by Aedes aegypti mosquitoes. Yogyakarta is an endemic area of DHF. One of the efforts of eradicating DHF in Yogyakarta was fogging with cypermethrin insecticide. Cypermethrin had been used since 2008 with a frequency of 1.469 times. However, repeated and prolonged application of chemical insecticide in an ecosystem unity may lead to vector resistance against the particular insecticide. Monitoring and early detection for the vector susceptibility status against insecticide was necessary in potential locations of DHF transmission, such as in elementary school. Detection of vector susceptibility status against insecticide could be conducted with susceptibility test using 0.05% cypermethrin impregnated paper.Objectives: To find out the status of Aedes aegypti susceptibility against cypermethrin insecticide and the relationship between the status of Aedes aegypti susceptibility with the frequency of cypermethrin application.Methods: An analytical observational research was conducted using cross-sectional design. Female Aedes aegypti from mosquito eggs collected at 72 state Elementary Schools in 45 villages in Yogyakarta were evaluated. Detection of Aedes aegypti susceptibility against cypermethrin was conducted using WHO standard method, namely, susceptibility test, which used 0.05% cypermethrin impregnated paper.Results: Aedes aegypti at elementary schools in Yogyakarta had been resistant against 0.05% cypermethrin, with an average mortality of 4.03%. No correlation between Aedes aegypti susceptibility in the elementary schools in Yogyakarta and the frequency of cypermethrin application. This might be attributable to the use of household insecticide and to the resistance history of the test animals.Conclusions: The population of Aedes aegyptiat the State Elementary Schools in Yogyakarta was found to be resistant against 0.05% cypermethrin. No relationship between Aedes aegypti susceptibility status and the frequency of cypermethrin application. Keywords: Aedes aegypti, Cypermethrin, impregnated paper, Susceptibility Test, INTISARI Pendahuluan: Demam Berdarah Dengue adalah penyakit infeksi yang disebarkan oleh nyamuk Aedes aegypti. Kota Yogyakarta merupakan daerah endemis DBD. Salah satu cara penanggulangan DBD di kota Yogyakarta dengan pengasapan menggunakan insektisida sipermetrin. Penggunaan sipermetrin sudah dilakukan sejak tahun 2008 dengan frekuensi aplikasi sebanyak 1469 kali. Aplikasi insektisida kimia dalam waktu lama dan berulang di satuan ekosistem dapat menimbulkan resistensi vector terhadap insektisida yang digunakan. Monitoring dan deteksi dini status kerentanan vector terhadap insektisida di kota Yogyakarta perlu dilakukan di lokasi yang berpotensi sebagai tempat penularan DBD diantaranya di sekolah dasar. Deteksi status kerentanan vector terhadap insektisida dapat dilakukan dengan susceptibility test menggunakan impregnated paper sipermetrin 0.05%.Tujuan: Mengetahui status kerentanan nyamuk Aedes aegypti di Lingkungan SDN di Kota Yogyakarta terhadap insektisida sipermetrin dan mengetahui hubungan status kerentanannya dengan frekuensi aplikasi insektisida sipermetrin.Metode: Penelitian ini merupakan penelitian observasional analitik dengan rancangan crosssectional. Subyek penelitian populasi nyamuk Aedes aegypti dari telur yang berasal dari 72 SDN di 45 kelurahan di Kota Yogyakarta. Deteksi status kerentanan nyamuk Aedes aegypti terhadap insektisida sipermetrin dilakukan dengan metode standar WHO susceptibility test menggunakan impregnated paper sipermetrin 0.05%.Hasil: Hasil uji kerentanan menunjukkan nyamuk Aedes aegypti di lingkungan sekolah dasar di kota Yogyakarta sudah resisten terhadap insektisida sipermetrin 0.05% dengan angka kematian nyamuk rata-rata 4.03%. Tidak ada korelasi antara status kerentanan nyamuk Aedes aegypti dengan frekuensi aplikasi insektisida sipermetrin. Hal ini bisa disebabkan karena penggunaan insektisida rumah tangga yang digunakan oleh masyarakat dan karena adanya riwayat resistensi dari nyamuk uji.Simpulan: Populasi nyamuk Aedes aegypti di lingkungan Sekolah Dasar Negeri di Kota Yogyakarta sudah resisten terhadap insektisida Sipermetrin 0.05%. Tidak ada hubungan status kerentanan nyamuk Aedes aegypti di lingkungan sekolah dasar negeri di Kota Yogyakarta dengan frekuensi aplikasi insektisida sipermetrin. Kata kunci: Aedes aegypti, Insektisida Sipermetrin, impregnated paper, Uji kerentanan, Sekolah Dasar